Łokieć tenisisty - przegląd wybranych metod fizykalnych, metod zaopatrzenia ortopedycznego i masażu = Tennis elbow ty - review of selected physical methods, methods of orthopaedic supplies and massage - Joanna Siminska; Katarzyna Pietkun; Joanna Stocka; Małgorzata Giermakowska; Krystyna Nowacka; Wojciech Hagner (Kazimierz Wielki University, 2015)
Siminska Joanna, Pietkun Katarzyna, Stocka Joanna, Giermakowska Małgorzata, Nowacka Krystyna, Hagner Wojciech. Łokieć tenisisty - przegląd wybranych metod fizykalnych, metod zaopatrzenia ortopedycznego i masażu = Tennis elbow ty - review of selected physical methods, methods of orthopaedic supplies and massage. Journal of Education, Health and Sport. 2015;5(2):269-280. ISSN 2391-8306. DOI: 10.5281/zenodo.16771 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A269-280 https://pbn.nauka.gov.pl/works/554272 http://dx.doi.org/10.5281/zenodo.16771 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015.   ŁOKIEĆ TENISISTY - PRZEGLĄD WYBRANYCH METOD FIZYKALNYCH, METOD ZAOPATRZENIA ORTOPEDYCZNEGO I MASAŻU TENNIS ELBOW TY - REVIEW OF SELECTED PHYSICAL METHODS, METHODS OF ORTHOPAEDIC SUPPLIES AND MASSAGE Siminska Joanna, Pietkun Katarzyna, Stocka Joanna, Giermakowska Małgorzata, Nowacka Krystyna, Hagner Wojciech Katedra i Klinika Rehabilitacji Collegium Medicum UMK w Bydgoszczy   Streszczenie   Obecnie szeroko rozpropagowany jest zdrowy i aktywny tryb życia. Dzisiaj dominuje moda za zdrowie i podejmowanie różnych form aktywności fizycznej. Nikogo zatem nie dziwi coraz większe zainteresowanie różnymi dyscyplinami sportu, zaczynając od biegania, przez fitness a kończąc na kulturystyce. Wzrost poziomu aktywności fizyczne i jej aktywnego podejmowania  jest zauważany nie tylko wśród ludzi zajmującymi się sportem zawodowo, ale również pośród amatorów, co jest obecnie bardzo popularne. Uprawianie sportu może niestety wiązać się z powstawaniem kontuzji oraz niechcianych urazów w obrębie układu mięśniowo-szkieletowego człowieka. Oczywiście wraz z podejmowanymi formami aktywności fizycznej mogą pojawiać się nieprzyjemne dolegliwości związane z odczuwaniem bólu w kościach, stawach, mięśniach czy ścięgnach. Te dolegliwości bólowe mogą występować również podczas wykonywania codziennych, rutynowych czynności życiowych. Ponadto grupą, która jest szczególnie narażona na takie niechciane urazy i dolegliwości bólowe są osoby pracujące fizycznie, wykonujące często powtarzalne ruchy. Często występują u nich powtarzające się mikrourazy. Z wiekiem mogą one przyczynić się do powstawania zwyrodnień. Jednym a takich przykładów mikrourazów w obrębie kończyny górnej jest łokieć tenisisty. Jedną ze skutecznych metod leczenia oprócz leczenia operacyjnego jest fizykoterapia. Działania te mogą zmniejszyć dolegliwości bólowe, a także zahamować niepożądane skutki mikrouszkodzeń w obrębie stawu łokciowego.   Słowa kluczowe: łokieć tenisisty, urazy, fizykoterapia, rehabilitacja.   Abstract   Now widely publicised is a healthy and active lifestyle. Today is dominated by the fashion for health and to undertake various forms of physical activity. It is not surprising, therefore anyone growing interest in different sports disciplines, from running for fitness and bodybuilding. The increase in the level of physical activity and its active making is perceived not only among people involved in the sport professionally, but also among amateurs, which is now very popular. Sporting may unfortunately be associated with the formation of an injury and unwanted injuries within the human musculoskeletal system. Of course, along with the measures taken by the forms of physical activity may appear unpleasant ailments related to the perception of pain in the bones, joints, muscles or tendons. These aches and pains can also occur when performing everyday, routine life. In addition, the group that is particularly vulnerable to such unwanted injuries and aches and pains are people working physically, often performing repetitive movements. Often occur in these repetitive microtrauma. With age they may contribute to the formation of postures. One such example of micro-injuries within the upper extremity is tennis elbow. One of the effective treatments in addition to surgical treatment is physical therapy. These actions can reduce aches and pains, as well as curb the adverse effects of microdamage of within the elbow joint.   Keywords: tennis elbow, injuries, physical therapy, rehabilitation.